Effect of Temperature and Roasting Time on the Quality of Argopuro Robusta Coffee - Bulqis, Malika; Arum, Ayu Puspita; Savitri, Dyah Ayu; Suud, Hasbi Mubarak (University of Jember, 2025)
The roasting process is a process that can determine the flavor and aroma released in coffee beans which is influenced by temperature treatment, and the length of the roasting process. The purpose of this study was to determine the effect of temperature and roasting time on the quality of Robusta Argopuro coffee. The experiment was conducted using a completely randomized design (CRD) factorial pattern with the treatment of roasting temperature variations of 190 ° C, 200 ° C, 210 ° C with a time of 10 minutes, 15 minutes and 20 minutes. Then the parameters of moisture content, pH value and caffeine content were observed as well as organoleptic tests in the form of color, taste and aroma. Data results were analyzed using analysis of variance, if there were significant differences, further tests were carried out using Duncan's multiple range test at the 5% level. Temperature and roasting time had a very significant effect on caffeine content, where the lowest caffeine content was in the combination of 200°C temperature treatment with 20 minutes roasting time. Moisture content and pH value had a very significant effect on roasting time, with the lowest moisture content and pH value obtained in 20 minutes of roasting, while roasting temperature had no significant effect on moisture content and pH value, but had a very significant effect on caffeine content. Based on the organoleptic test, panelists preferred the Argopuro Robusta coffee brew at a temperature of 200°C with a roasting time of 15 minutes.